THE TRANSFORMATIONAL EVOLUTION OF THE ROMANIAN INTELLIGENCE SERVICE-SRI IN THE LIGHT OF THE SECURITY SECTOR REFORM - Iulia-Mihaela DRĂGAN (Romanian Intelligence Studies Review)
The importance of the security sector reforms in Europe became significant with the collapse of the communist bloc at the end of 1989 in relation to the need to implement democratic instruments. At the same time, until now, the implications of the reforms of the intelligence sector, are being discussed by virtue of the need to quickly adapt to the requirements of the security environment and the dynamics of threats at the international level. For Romania, the reform of the intelligence sector was one of the most pressing needs following the collapse of the communist regime and the establishment of a new intelligence service, the Romanian Intelligence Service (SRI), so that in less than thirty years, Romania will be represented in the intelligence community by one of the most performing and prestigious intelligence services at the international level. Therefore, this article analyses the applicability of the theory of security sector reform, in relation to the evolution of the transformations achieved within the Romanian Intelligence Service. As the intelligence services represent a category of the core actors of the security sector in a state, this article aims to gradually evaluate the implementation of the reform attributes using a methodology based on the analysis of activity reports and relevant public documents, starting from the establishment of SRI to present. Complementary, with regards to the public interest, the purpose of the article is to increase the awareness of civil society in the intelligence sector, by dismantling the conspiratorial narrative and highlighting the risks generated by the assimilation of disinformation elements aimed at the service’s activity, while also highlighting the transformational evolution of the Romanian Intelligence Service regarding the elements of democratization.